2021
DOI: 10.1111/ibi.12951
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in genetic knowledge affect conservation management of kiwi (Apteryx) species

Abstract: Worldwide, there is growing appreciation of the importance of integrating genetic information into conservation management. However, there are commonly occurring problems which impact on doing this successfully. This issue is well illustrated by kiwi Apteryx species. Like many endangered taxa, extant kiwi populations are small, fragmented and isolated, raising concerns of potential inbreeding depression. Accordingly, kiwi conservation includes discussion of genetic management and translocations. To date, kiwi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…The potentially extensive impact of breeding systems and their variability highlights the need to incorporate breeding biology into the already challenging field of predicting translocation outcomes (Undin, Hills, Lockhart, & Castro, 2021a; Undin, Lockhart, Hills, & Castro, 2021b). As described above, resource distribution is one of the main factors determining breeding systems, and breeding systems as well as mating strategies can change with population density, habitat, and/or availability of territories and mates (Carrete et al, 2006; Griffith et al, 2010; Heinsohn et al, 2019; Pribil & Searcy, 2001; Walker et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potentially extensive impact of breeding systems and their variability highlights the need to incorporate breeding biology into the already challenging field of predicting translocation outcomes (Undin, Hills, Lockhart, & Castro, 2021a; Undin, Lockhart, Hills, & Castro, 2021b). As described above, resource distribution is one of the main factors determining breeding systems, and breeding systems as well as mating strategies can change with population density, habitat, and/or availability of territories and mates (Carrete et al, 2006; Griffith et al, 2010; Heinsohn et al, 2019; Pribil & Searcy, 2001; Walker et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these activity registering transmitters have greatly increased the potential for studying kiwi ecology, incubation behavior, and breeding success rate (e.g., Bansal, 2020; Cunningham & Castro, 2011; Dixon, 2015; Hiscox, 2014; Wilson, 2014; Ziesemann et al, 2011). This progress is important as many questions remain unanswered, not the least regarding how to optimize kiwi translocations and further incorporate behavior in conservation management (Jahn et al, 2022; Undin, Hills, Lockhart, & Castro, 2021a; Undin, Lockhart, Hills, & Castro, 2021b).…”
Section: The Increasingly Less Elusive Kiwimentioning
confidence: 99%
See 1 more Smart Citation
“…A first step would be to further examine the genetic dissimilarity between partners and investigate if it is predominantly linked to and/or exaggerated in certain regions of the genome (Beaumont and Balding, 2004;Fitzpatrick et al, 2010;Keller et al, 2013). Such studies would not only increase our understanding of Apteryx breeding but also take us closer to understanding the significance and nature of the genetic differences observed between Apteryx taxa today (see Undin et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Weir et al (2016) found a Pairwise Hudson's F st of 0.139 (95% CI 0.120-0.158) between the Northland and Western taxa, and dated the split between these management units, and thus between the parental populations of Ponui Island, to between 100,000 and 220,000 years ago. Whilst local adaptations might have evolved over this period of temporal divergence, the extent and nature of any local adaptation remains unknown (Undin et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%